ANALYSIS OF THE EFFECT OF FINANCIAL RATIOS AND THE COVID-19 PANDEMIC ON FINANCIAL DISTRESS OF JOINT VENTURE LIFE INSURANCE COMPANIES IN INDONESIA - Husein Triarso; Harjum Muharam (Jurnal Apresiasi Ekonomi, 2025)
The study was conducted to analyze the effect of financial ratios and the Covid pandemic on the financial distress of joint venture life insurance companies in Indonesia during the period 2017 to 2021. The quantitative approach is a research method used through testing with logistic regression analysis in the SPSS 25 program. The data source comes from the annual audit report and has been submitted to the Financial Services Authority. The type of data used is secondary data based on the financial statements of joint venture life insurance companies.The study concluded that the ROA and Equity ratio indicators have a significant negative effect on financial distress. Furthermore, other financial ratios, namely Liquidity, RBC, RKI, Claim ratio and the Covid Pandemic, do not affect the financial distress of joint venture life insurance companies. This study provides suggestions for OJK to continue using Equity and add ROA to the Early Warning System (EWS) used so that it can provide comprehensive information regarding the health condition of insurance companies. Keywords: Financial Distress, Financial Ratios, Joint Venture Life Insurance